2012
DOI: 10.1155/2012/423801
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nursing Home Hearing Handicap Index with Audiological Findings: A Presbycusis Study

Abstract: Hearing evaluation usually includes hearing threshold assessment, middle ear function, and word recognition tests that lead to an accurate result of peripheral and central auditory system. However, they have some limitations because they cannot fully encompass all aspects of hearing loss problems. Using self-assessment approach, via a questionnaire or telephone survey, is one of the easiest methods to study hearing loss in population. In this research, 60 nursing home residents (27 females and 33 males) rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In this study, interviewed nurses notably acknowledged the relationship between hearing and vision, and quality of life (QoL), and how impairment in either can negatively influence the individual’s functioning as a whole, as well as their access to social engagement and participation. Research has shown that even without cognitive impairment, the ability to perform activities of daily living (ADLs), along with the QoL of LTCH residents, is significantly related to the presence of eye disorders or visual impairment [ 47 , 58 61 ]. Likewise, access to social opportunities and QoL, is negatively impacted by hearing impairments [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, interviewed nurses notably acknowledged the relationship between hearing and vision, and quality of life (QoL), and how impairment in either can negatively influence the individual’s functioning as a whole, as well as their access to social engagement and participation. Research has shown that even without cognitive impairment, the ability to perform activities of daily living (ADLs), along with the QoL of LTCH residents, is significantly related to the presence of eye disorders or visual impairment [ 47 , 58 61 ]. Likewise, access to social opportunities and QoL, is negatively impacted by hearing impairments [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Hearing Handicap Inventory for the Elderly-Screening (HHIE-S) is a subjective examination, consisting of 10 questionnaires assessing the effect of hearing loss on emotional and social outcomes with a total score between 0 and 40 [6,9]. The HHIE-S questionnaire can be used as a screening tool to identify handicaps due to hearing loss in the elderly [3].…”
Section: Methodsmentioning
confidence: 99%